On the dual-stacking transition to IPv6: A forlorn hope? - Dell, Peter (Pergamon, 2018)
© 2018 Elsevier Ltd The assumption that IPv6 will inevitably replace IPv4 as the dominant network layer protocol on the Internet is almost universal. A failure of IPv6 to diffuse is thought to have far-reaching and long-lasting economic and social consequences, yet there have been no prior analyses of the dual-stacking transition mechanism by which IPv6 diffusion is expected to be achieved in order to understand whether it is likely to succeed. Guided by economic theory, this paper presents such an analysis, and concludes that the dual-stacking transition strategy is unlikely to work, leaving the Internet with no workable means of achieving migration to IPv6. The paper concludes with a number of recommendations for regulatory and policy bodies, end-user organisations and network operators.